2008
DOI: 10.1111/j.1365-2672.2008.03932.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of culturable and nonculturableLegionellaspecies from hot water systems of public buildings in Japan

Abstract: Aims:  To investigate the prevalence of culturable and nonculturable Legionella species in hot water systems of public buildings in Japan and assess the risk factors associated with Legionella contamination in hot water systems. Methods and Results:  Legionella species were detected by conventional culture and molecular methods in 130 water samples collected from 40 buildings. A total of 26 (20·0%) water samples from 17 (42·5%) buildings were positive by culture, qualitative PCR or both methods: Legionella pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 56 publications
5
43
1
4
Order By: Relevance
“…Our data are largely in agreement with other works indicating that strains of L. pneumophila, the species mostly associated to legionellosis, are those mostly often found to contaminate taps of private apartments, hotels and hospitals in Italy [13] as well as buildings in Hungary, Germany, the USA and Japan [14][15][16]23]. Nevertheless, we also recovered several isolates of L. anisa, a species already found in building plumbing [14] and known to be associated with human infections as one of the pathogens causing Pontiac fever [1]; as well as one isolate identified as L. tauriniensis, a species recently isolated from a hospital humidifier in Turin, Italy [24] but never linked to human disease. Since several isolates were cultured from each water sample, all the sequences were aligned, and a representative one was chosen from each group of isolates obtained from the same control-point tap and identified as the same Legionella species.…”
Section: Phylogenetic Analysissupporting
confidence: 93%
See 2 more Smart Citations
“…Our data are largely in agreement with other works indicating that strains of L. pneumophila, the species mostly associated to legionellosis, are those mostly often found to contaminate taps of private apartments, hotels and hospitals in Italy [13] as well as buildings in Hungary, Germany, the USA and Japan [14][15][16]23]. Nevertheless, we also recovered several isolates of L. anisa, a species already found in building plumbing [14] and known to be associated with human infections as one of the pathogens causing Pontiac fever [1]; as well as one isolate identified as L. tauriniensis, a species recently isolated from a hospital humidifier in Turin, Italy [24] but never linked to human disease. Since several isolates were cultured from each water sample, all the sequences were aligned, and a representative one was chosen from each group of isolates obtained from the same control-point tap and identified as the same Legionella species.…”
Section: Phylogenetic Analysissupporting
confidence: 93%
“…Nevertheless, only a few papers have investigated the presence of Legionella in this kind of system, and none in university buildings. Our data indicated that the contamination rate recorded in the University of Perugia buildings was lower than that found in offices or schools in other countries, ranging from more than 30% in Germany [16] to 60% in Japan and Hungary [14,15], and even lower than the 30.5% rate recorded in private apartments in Italy [13]. Moreover, even if many of the buildings at the University of Perugia are very ancient (ranging in age from the 1960s back to the 13th century) and it has been previously shown that the rate of positive samples increases with the age of the building [15], we found that only 1 of the 12 contaminated buildings was older than one century, while all the others were very recent (i.e., less than 30 years-old).…”
Section: Rate Of Legionella Colonizationcontrasting
confidence: 57%
See 1 more Smart Citation
“…Several species of the Legionella genus are responsible for LD; however, L. pneumophila is responsible for the majority of cases of LD, with Ͼ90% of all identified clinical cases within serogroup 1, which accounts for ϳ85% of all cases (2,3). The organism is quite ubiquitous in aqueous environments, whether natural or artificial (4).…”
mentioning
confidence: 99%
“…In recent years, contamination of water systems has gradually become recognized as an important risk factor all over the world, [39][40][41][42][43][44] and many cases of Legionnaires' disease have been detected in Legionella-contaminated water systems.…”
Section: Discussionmentioning
confidence: 99%